The longitudinal relationship between maternal bonding and mental health during the COVID-19 pandemic - Reck, Corinna; Tettenborn, Alexandra von; Woll-Weber, Christian F. J.; Küçükakyüz, Su Mevsim; Megele, Martina J.; Kaubisch, Lea; Marx, Anton; Hagl, Maria; Nonnenmacher, Nora; Müller, Mitho; Zietlow, Anna-Lena (Journal of reproductive and infant psychology, 2025)
A strong maternal bond to the infant has been shown to be important for child development and to be related to maternal mental health, for example to postpartum depression. During the COVID-19 pandemic, rates of maternal depression increased and some studies suggest that maternal bonding was also affected by the stressful circumstances related to the pandemic. Our aim was to examine the relationship between maternal bonding, depressive symptoms and perceived stress during the pandemic. Five hundred and eighty-nine mothers of young children (mostly aged 0-3 years) participated in a longitudinal online survey. Data regarding maternal bonding, depressive symptoms and perceived stress was taken at two time points, the first (T1) with few pandemic-specific restrictions and the second (T2) while more pandemic-specific restrictions were in place (e.g. closures of day care facilities). Cross-lagged panel modelling (CLPM) was applied for analysis. Bonding, depressive symptoms and perceived stress significantly worsened from the first to the second time point (effect sizes d = 0.35, d = 0.56 and d = 0.49). CLPM strongly suggested cross-lagged, reciprocal predictions between depressive symptoms and perceived stress as well as a significant prediction of stress at T2 by bonding at T1, with a small effect (β = .08, p < .05). This study shows that maternal mental health deteriorated during the pandemic and that bonding influenced these dynamics. In light of the importance of maternal bonding for child development, strengthening this bond can be considered a preventive measure to support mothers in times of crisis.